TANGGAPAN PASIEN TERHADAP PELAYANAN KESEHATAN DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT TINGKAT II MOH. RIDWAN MEURAKSA - Agus Sumarno; Tri Pamularsih (Jurnal Afiat : Kesehatan dan Anak, 2019)
Introduction preliminary health services are one of the determinants of the good and bad of the hospital's image, therefore the quality of health services needs to be considered and optimally improved. Satisfaction is the level of state that is felt in accordance with patient expectations from the results of consumer assessments that the service has provided a level of fulfillment of pleasure for patients, health service providers include doctors, nurses and administration. The purpose of this study was to determine the response of patients to health services in the disease clinic at Moh. Ridwan Meuraksa. The research method of research design is descriptive statistics. The study population numbered 300 patients using the Solvin formula obtained 75 respondents. Data collection using a questionnaire instrument. Data analysis uses percentages (%) and average values ​​(). The results of Emphaty's research are in the Good category, Responsibility in the Good enough category, Assurance in the Good category, Reability in the Good enough category, Tangible in the Very good category. Conclusion 17.3% of doctors started the service not according to the specified schedule. 24% of doctors have not explained the disease to patients. Suggestions for patient satisfaction and improving the quality of services can include health workers in seminars, training, and health education so that health workers can provide patient satisfaction with internal medicine polyclinic services.